Minyak Zaitun Sebagai Pengganti Xylene pada Prosesing Jaringan Histologis untuk Pewarnaan Kulit dan Hepar Mencit dengan Hematoxylin Eosin: Sebuah Studi Perbandingan - Eko Naning Sofyanita; Arya Iswara; Djoko Priyatno (Jaringan Laboratorium Medis, 2022)
Clearing results in histological processing can be affected due to tissue density and viscosity of the clearing agent. Xylene is the most commonly used aromatic solvent for clearing agents and deparaffinizing agents in histopathology laboratories, but xylene is one of the most dangerous chemicals found in histology laboratories. Based on the dangers posed by xylene, a replacement material is needed. Several xylene substitutes such as reagents derived from limonene, aliphatic hydrocarbons, vegetable oils and mineral oils have been commercially developed, but the available xylene substitutes are still less effective, more expensive, and still as dangerous as xylene itself. Substitutes that are considered safer are from natural oils, one of which is olive oil which has similarities with xylene, namely in hydrocarbon and phenol compounds. This study used two types of tissue, namely skin and liver from mice (Mus musculus) which were cut into two parts; the first part uses xylene as and the other part uses olive oil as a clearing agent. The assessment of hematoxylin eosin staining results were determined based on the category of assessment of cell structure, such as the cell nucleus, cytoplasm, and color uniformity carried out by three readers and five fields of view for each microscopic slide at 40X magnification of the objective lens. Comparison of observations of the xylene group in skin and liver tissue 100% got a good score on the cell nucleus, cytoplasm, and color uniformity. (p=1,000). The olive oil group had a slight difference in color uniformity in liver tissue when compared to skin, but not statistically different (p=0.773). The comparison of the overall readings of the xylene and olive oil groups on skin and liver tissue also showed no statistically different (p=0.262). So it can be concluded that olive oil can be recommended as a substitute for xylene in the clearing process in histological tissue processing.